2008
DOI: 10.1016/j.yebeh.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A single early-life seizure impairs short-term memory but does not alter spatial learning, recognition memory, or anxiety

Abstract: The impact of a single seizure on cognition remains controversial. We hypothesized that a single early life seizure (sELS) on rat post-natal day (P) 7 would alter only hippocampal-dependent learning and memory in mature (P60) rats. The Morris Water Maze (MWM), Novel Object and Novel Place Recognition (NOR/NPR) tasks, and Contextual Fear Conditioning (CFC) were used to assess learning and memory associated with hippocampal/prefrontal cortex, perirhinal/hippocampal cortex, and amygdala function, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 76 publications
4
49
0
Order By: Relevance
“…15 induced by KA (Cornejo et al, 2008, Cornejo et al, 2007. Thus, our findings add to the reports of long-term cellular defects that can be induced by a single neonatal seizure.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
See 1 more Smart Citation
“…15 induced by KA (Cornejo et al, 2008, Cornejo et al, 2007. Thus, our findings add to the reports of long-term cellular defects that can be induced by a single neonatal seizure.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
“…Even a single seizure induced by PTZ in P1 rats leads to disrupted hippocampal physiology when examined at 2-3 months of age (Zhao et al, 1994). Similarly, a single kainic acid (KA) seizure in P7 rats has been reported to permanently disrupt assembly of glutamatergic synapses and short-term memory of rats when examined at P60 (Cornejo et al, 2008, Cornejo et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…While initial studies using acute seizures reported minimal long term consequences (such as morphological damage), later studies using multiple or more severe seizures demonstrated anatomical changes (Holmes et al, 1998) often correlating with abnormal behavioral (de Rogalski Landrot et al, 2001) and altered seizure threshold (Lynch et al, 2000). More recent studies using single, mild seizures demonstrate long term behavioral and physiological changes (Bernard et al, 2013, 2014; Cornejo et al, 2007, 2008; Lynch et al, 2000; Sayin et al, 2004) without anatomical abnormalities. Rodent models of ELS are reviewed to explore their construct validity (i.e., relationship of triggering mechanisms to human disease) and then examined for evidence of the development of the ASD/ID behavioral phenotype following ELS.…”
Section: Introductionmentioning
confidence: 99%
“…The percent of time that mice stayed in the center (center staying %) was measured to assess anxiety. Moreover, total moving time (sec) and total moving distance (cm) were measured to assess the amount of movement [17].…”
Section: Open-field Testmentioning
confidence: 99%
“…They were allowed to explore the maze for 10 min. The anxiety score was defined as time spent in the open arms (sec), and total moving time (sec) was measured to evaluate the amount of activity [17].…”
Section: Elevated Plus Mazementioning
confidence: 99%